2016
DOI: 10.1007/s00223-016-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone (1–34) Transiently Protects Against Radiation-Induced Bone Fragility

Abstract: Radiation therapy for soft tissue sarcoma or tumor metastases is frequently associated with damage to the underlying bone. Using a mouse model of limited field hindlimb irradiation, we assessed the ability of parathyroid hormone (1–34) fragment (PTH) delivery to prevent radiation-associated bone damage, including loss of mechanical strength, trabecular architecture, cortical bone volume, and mineral density. Female BALB/cJ mice received four consecutive doses of 5 Gy to a single hindlimb, accompanied by daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Using a mouse model of unilateral hindlimb limited field radiotherapy, we have previously demonstrated that therapeutic radiation results in loss of femoral metaphyseal trabecular structures (decreased trabecular bone volume fraction, decreased trabecular number, decreased connectivity density, and increased trabecular spacing) subsequent to increased osteoclastic activity, diminished bone strength (axial compression testing of distal femur, femoral diaphyseal bending strength), and decreased femoral diaphyseal fracture toughness without loss of bone density. [11][12][13][14] Work in other labs has supported these findings. [15][16][17] Furthermore, we have shown that the bone matrix (organic and collagen phases) becomes increasingly aligned post-RTx, accompanied by an increase in trivalent:divalent collagen crosslink ratio as measured by Raman spectroscopy, with only small transient changes in pathologic crosslinks and adducts such as advanced glycation end products (AGEs).…”
mentioning
confidence: 59%
“…Using a mouse model of unilateral hindlimb limited field radiotherapy, we have previously demonstrated that therapeutic radiation results in loss of femoral metaphyseal trabecular structures (decreased trabecular bone volume fraction, decreased trabecular number, decreased connectivity density, and increased trabecular spacing) subsequent to increased osteoclastic activity, diminished bone strength (axial compression testing of distal femur, femoral diaphyseal bending strength), and decreased femoral diaphyseal fracture toughness without loss of bone density. [11][12][13][14] Work in other labs has supported these findings. [15][16][17] Furthermore, we have shown that the bone matrix (organic and collagen phases) becomes increasingly aligned post-RTx, accompanied by an increase in trivalent:divalent collagen crosslink ratio as measured by Raman spectroscopy, with only small transient changes in pathologic crosslinks and adducts such as advanced glycation end products (AGEs).…”
mentioning
confidence: 59%
“…Work in mouse models (total body and limited field RTx) consistently demonstrates an early increase in osteoclast numbers at 1 to 2 weeks post‐RTx, followed by long‐term depletion of osteoclasts . This results in early loss of trabecular bone and persistence of highly cross‐linked, highly aligned bone matrix due to loss of remodeling activity . At this point, it is unknown whether loss of local osteoclasts after limited field irradiation is because of 1) the absence of osteoclast progenitor cells, or 2) an inability of osteoclast precursors to multinucleate, differentiate, or adhere.…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) This results in early loss of trabecular bone and persistence of highly cross-linked, highly aligned bone matrix due to loss of remodeling activity. (16,17,21,33) At this point, it is unknown whether loss of local osteoclasts after limited field irradiation is because of 1) the absence of osteoclast progenitor cells, or 2) an inability of osteoclast precursors to multinucleate, differentiate, or adhere. Using this mouse model, we have previously shown that mineral apposition rate is not decreased post-RTx.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its use in severely osteoporotic patients, intermittent administration of parathyroid hormone may be a useful drug to decrease bone loss and reduce the risk of fracture. The use of PTH has been investigated in a series of studies by Oest and colleagues [51,75]. In the first, they investigated the impact of PTH on bone fragility in a mouse hind limb model.…”
Section: Pth and Blocking Sclerostinmentioning
confidence: 99%